Case reportExtrapulmonary tuberculosis following allogeneic stem cell transplantation – a difficult and late diagnosis - Tomaszewska, Agnieszka; Nasiłowska-Adamska, Barbara; Prochorec-Sobieszek, Monika; Hałaburda, Kazimierz; Szczepiński, Andrzej; Mariańska, Bożena (Archives of Medical Science, 2009)
Tuberculosis, especially with the extrapulmonary manifestation, is usually not considered as the first line in the differential diagnosis in patients after stem cell transplantation. We report a case of a 54-year old man after reduced intensity conditioning regimen allogeneic stem cell transplantation, without known personal or family history of tuberculosis, who presented knee joint, skin and bone marrow involvement by a Mycobacterium tuberculosis infection. A delay from the onset of the first symptoms to the confirmed diagnosis of tuberculosis was about 2 months in this case. Despite this delay, our patient successfully recovered after 4-tuberculostatics followed by 2-tuberculostatics therapy.